2017
DOI: 10.1186/s13000-017-0619-2
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar ependymoma with overlapping features of clear-cell and tanycytic variants mimicking hemangioblastoma: a case report and literature review

Abstract: BackgroundImaging and histology of clear-cell ependymoma and cerebellum-based hemangioblastoma are similar; distinguishing between them is a diagnostic challenge.Case presentationA 62-year-old Chinese woman presented with an intermittent headache of 8 years’ duration. Computed tomography and magnetic resonance imaging revealed a mass in the cerebellum. Neurological imaging suggested hemangioblastoma (HB). Histologically, the tumor included cellular and paucicellular areas, in which cells were arranged in nests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 27 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…CCE express glial fibrillary acidic protein (GFAP) and its intensity is stronger and more extensive than in HB. 12) In addition, our group had reported that 201 Tl-SPECT can help to differentiate between cerebellar CCE and HB to establish the correct preoperative diagnosis, however, not performed in this case unfortunately. 10) …”
Section: Discussionmentioning
confidence: 79%
“…CCE express glial fibrillary acidic protein (GFAP) and its intensity is stronger and more extensive than in HB. 12) In addition, our group had reported that 201 Tl-SPECT can help to differentiate between cerebellar CCE and HB to establish the correct preoperative diagnosis, however, not performed in this case unfortunately. 10) …”
Section: Discussionmentioning
confidence: 79%
“…So, according to the imaging ndings of this patient, the ependyma, central neurocytoma and choroidal papilloma were mainly considered in the differential diagnosis of tumors in the lateral ventricle. [20][21][22] To diagnose the intracranial hemangioblastoma, MRI is superior to CT. 23 On MRI, there are several types of hemangioblastoma 2,24−25 : (1) Large unenhanced cyst with enhanced small nodule; (2) Simple cyst without enhancement; (3) Simple cyst with enhanced wall; (4) The cyst with enhanced wall is accompanied by enhanced small nodule. In this case, the tumor was consistent with the last type.…”
Section: Discussionmentioning
confidence: 99%
“…There were six cases with the synchronous occurrence of HCC and RCC reported in the literature (Table 1) [11][12][13][14][15][16] . The median age was 55 years (42-72).…”
Section: Discussionmentioning
confidence: 99%